Increasing Returns in Infinite-Horizon Economies - Shannon, Chris (Review of Economic Studies, 1997)
This paper shows that in a general equilibrium model with an infinite horizon in which production may exhibit increasing returns to scale or non-convexities, marginal cost pricing equilibria exist and are essential, that is, stable with respect to small perturbations of the economy. As in many important models of market imperfections, marginal cost pricing equilibria need not be Pareto optimal in the presence of non-convexities, so the systematic approaches to equilibrium analysis in infinite-dimensional commodity spaces, which rely crucially on the First Welfare Theorem, cannot be used. Instead, this paper introduces Leray-Schauder degree theory, the extension of degree theory to Banach and locally convex spaces, as the natural methodology for showing that equilibria exist and for analyzing qualitative features of equilibria such as local uniqueness or essentiality.